A MADS-box transcription factor, SlMADS1, interacts with SlMACROCALYX to regulate tomato sepal growth. (September 2022) - Xing, Mengyang; Li, Hongli; Liu, Gangshuai; Zhu, Benzhong; Zhu, Hongliang; Grierson, Donald; Luo, Yunbo; Fu, Daqi
Abstract: In flowering plants, sepals play important roles in the development of flowers and fruit, and both processes are regulated by MADS-box (MADS) transcription factors (TFs). SlMADS1 was previously reported to act as a negative regulator of fruit ripening. In this study, expression analysis shown that its transcripts were very highly expressed during the development of sepals. To test the role of SlMADS1, we generated KO- SlMADS1 (knock-out) tomato mutants by CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats and CRISPR-associated protein 9) technology and over-expression of SlMADS1 (OE- SlMADS1 ). The sepals and individual cells of KO- SlMADS1 mutants were significantly elongated, compared with the wild type (WT), whereas the sepals of OE- SlMADS1 tomatoes were significantly shorter and their cells were wider. RNA-seq (RNA-sequencing) of sepal samples showed that ethylene-, gibberellin-, auxin-, cytokinin- and cell wall metabolism-related genes were significantly affected in both KO- SlMADS1 and OE- SlMADS1 plants with altered sepal size. Since SlMACROCALYX (MC) is known to regulate the development of tomato sepals, we also studied the relationship between SlMC and SlMADS1 and the result showed that SlMADS1 interacts directly with SlMC. In addition, we also found that manipulating SlMADS1 expression alters the development of tomato plant leaves, roots and plant height. These results enrich our understanding of sepal development and the function of SlMADS1 throughout the plant. Highlights: SlMADS1 is highly expressed during the development of sepals. The sepals and individual cells of KO- SlMADS1 mutants are significantly elongated and the inverse phenotypes are detected in OE- SlMADS1 lines. SlMADS1 interacts with MACROCALYX (MC). Manipulating SlMADS1 expression alters the sepal length of tomato fruit.